Riboflavin–citrate conjugate multicore SPIONs with enhanced magnetic responses and cellular uptake in breast cancer cells. Issue 8 (22nd March 2022) - Mekseriwattana, Wid; Guardia, Pablo; Herrero, Beatriz Torres; de la Fuente, Jesus M.; Kuhakarn, Chutima; Roig, Anna; Katewongsa, Kanlaya Prapainop
Abstract : Riboflavin-coated multicore SPIONs show specific binding with RCP, enhanced uptake in breast cancer cells and excellent MRI response. Abstract : Breast cancer accounts for up to 10% of the newly diagnosed cancer cases worldwide, making it the most common cancer found in women. The use of superparamagnetic iron oxide nanoparticles (SPIONs) has been beneficial in the advancement of contrast agents and magnetic hyperthermia (MH) for the diagnosis and treatment of cancers. To achieve delivery of SPIONs to cancer cells, surface functionalization with specific ligands are required. Riboflavin carrier protein (RCP) has been identified as an alternative target for breast cancer cells. Here, we report a novel riboflavin (Rf)-based ligand that provides SPIONs with enhanced colloidal stability and high uptake potential in breast cancer cells. This is achieved by synthesizing an Rf-citrate ligand. The ligand was tested in a multicore SPION system, and affinity to RCP was assessed by isothermal titration calorimetry which showed a specific, entropy-driven binding. MRI and MH responses of the coated Rf-SPIONs were tested to evaluate the suitability of this system as a theranostic platform. Finally, interaction of the Rf-SPIONs with breast cancer cells was evaluated by in vitro cellular uptake in MCF-7 breast cancer cells. The overall characterization of the Rf-SPIONs highlighted the excellent performance of this platform for theranostic applications in breast cancer.